PELAKSANAAN PROGRAM WORKSHOP â€œBELAJAR EFEKTIFâ€ UNTUK ORANG TUA - Suprayekti Suprayekti; Septyara Dwi Anggraeni (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2017)
This study aims to obtain a clear picture of the implementation of the â€œEffective Learningâ€ workshop programs for parents at Yayasan Rangkul Keluarga Kita which was held in November 2016-January 2017 in South Jakarta. This research uses a descriptive method with a survey technique. Data collection techniques used were direct observation, document observation, questionnaires, and interviews. The result of this study is description obtained from the implementation of learning â€œEffective Learningâ€ based on planning, implementation, and evaluation. In order for the learning process to work properly, facilitators involve learners to formulate workshop objectives.